2020
DOI: 10.1016/j.molcel.2020.02.020
|View full text |Cite
|
Sign up to set email alerts
|

Ago2-Dependent Processing Allows miR-451 to Evade the Global MicroRNA Turnover Elicited during Erythropoiesis

Abstract: Highlights d miR-451 is the most abundant miRNA in erythrocytes and is clustered with miR-144 d miR-144 targets Dicer in a negative-feedback loop during erythropoiesis d miR-451 is refractory to the loss of Dicer due to its Ago2dependent processing d miR-144 influences the processing of miR-451 in trans

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
87
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(99 citation statements)
references
References 42 publications
6
87
0
1
Order By: Relevance
“…It has been previously shown that Argonauts generate small RNAs in a dicer-independent mechanism (60,63,64), and our data suggests that Ago1 in planarians may be involved in the dicer-independent processing and/or maintaining the stability of the itRFs.…”
Section: Ago1-based Processing Of Itrfs In S Mediterraneasupporting
confidence: 64%
See 1 more Smart Citation
“…It has been previously shown that Argonauts generate small RNAs in a dicer-independent mechanism (60,63,64), and our data suggests that Ago1 in planarians may be involved in the dicer-independent processing and/or maintaining the stability of the itRFs.…”
Section: Ago1-based Processing Of Itrfs In S Mediterraneasupporting
confidence: 64%
“…Interestingly, tRF-5s that were implicated to undergo Dicer-based cleavage in other systems (75,76) also remained unaltered in Dicer KD suggesting that tRFs in planarians are Dicer-independent. However, in several systems, Argonauts have been shown to process of small RNAs in a dicer-independent pathway (60,63,64). Planarian Ago2 has been suggested to be critical for miRNA-based regulation (62) while the function of Ago1 remains unexplored.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, during erythropoiesis, miR‐144 targets DICER in a negative feedback loop, leading to the inhibition of canonical miRNA processing. Otherwise, DICER‐independent miR‐451 processing is undisturbed (Kretov et al, 2020).…”
Section: Mirna Biogenesismentioning
confidence: 99%
“…These intermediates are trimmed to 20–26 nt mature miRNAs (Pan et al, 2015; Yoda et al, 2013). During biogenesis, the passenger strand is not generated, which makes this miRNA a promising tool due to its limited off‐targets (Kretov et al, 2020). Konstantinova's group successfully used this backbone for the expression of siRNA targeting the HTT transcript, and a phase I/II clinical trial for this amiRNA in HD began this year.…”
Section: Artificial Mirna Scaffoldsmentioning
confidence: 99%
“…Drosha cleaves pre-miR-451, which is loaded directly into AGO2; it is responsible for 3′-end trimming and maturation of pre-miR-451. Poly(A)-specific ribonuclease (PARN) trims down the 3′ end of AGO2-cleaved pre-miR-451 to produce mature miR-451 [ 31 ]. Finally, XPO5 independent transport of pre-miRNA from the nucleus to cytoplasm has been described in the case of miR-320 family, as these miRNAs use the complex of XPO1 and PHAX (phosphorylated adaptor for RNA export) proteins for their transport [ 32 ].…”
Section: History Of Microrna Discoverymentioning
confidence: 99%